Peru : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Peru. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
After being hit very hard by the pandemic in 2020, both in terms of health and economic outcomes, Peru experienced an equally strong economic rebound in 2021. A new administration was inaugurated in July 2021 with a program focused on reducing inequality and improving social conditions, but limited support from Congress and lack of cohesion heightened political uncertainty. While real GDP surpassed its pre-pandemic level by 2021, labor force participation and total employment have not fully recovered yet. Poverty increased significantly in 2020 and, despite some improvement in 2021, remains higher than in 2019. On May 27, 2021, the IMF Executive Board completed the mid-term review of Peru's continued qualification under the Flexible Credit Line (FCL) arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Peru